Assessing the potential impacts of COVID-19 in Brasil: Mobility, Morbidity and Impact to the Health System - Coelho, Flávio Codeço (2020)
The two largest Brazilian cities, Rio de Janeiro and São Paulo, have declared community transmission of COVID-19 on mid March, 2020. In this study we estimated the most vulnerable areas in Brazil for COVID-19, both in terms of risk of introduction and risk of mortality associated with social vulnerability. We explore the most likely routes of spread through the country, from the already exposed cities, according to human mobility statistics. The resulting maps should help authorities in their efforts to prioritize actions and if resource allocation to mitigate the effects of the pandemic.